The uptake of unmanned aerial vehicles in the urban environment - Ferreira, Tomás Lencastre Megre (2021)
World's current mobility systems are often inefficient and unsustainable, therefore the need for new schemes to satisfy mobility needs appears. This quest has given the impetus to the industry to invest in new technologies such as autonomous systems enabling self-driving vehicles. In this context, the concept of Urban Air Mobility (UAM), a term used for short-distance, on-demand, highly automated, passenger or cargo-carrying air mobility services, has arisen. This thesis presents the introduction phase of strategic planning for the era of urban air mobility focusing on the user and citizen acceptance of the system required for its operation. A survey is designed to capture the perception of citizens and potential users on aspects such as safety, security, the well-being of the society (including issues of aesthetics, quality of life, social impacts), driving behaviour, mobility behaviour, expected benefits and their impact on the acceptance and the intention to use these systems. The acceptance of citizens and potential users (considered as two different groups) is also analysed in terms of its potential uses (e.g. health emergencies, leisure, connectivity to remote regions). The survey is applied to Portugal area and 391 responses were gathered. The collected data is analysed through correlation analysis, ANOVA and non-parametric analysis. The thesis introduces a framework of analysis for the introduction of Unmanned Aerial Vehicles. This study will reveal which are the main factors that have an impact on citizens' embracement and intention to use this new transport mode and that should be considered by stakeholders.